Le travail et l’emploi à l’épreuve du VIH/VHC : régulations des systèmes d’activités et réévaluation du modèle de vie - Dominique Lhuilier; Sandra Amado; Frédéric Brugeilles; Mariama Diallo; Dominique Rolland (Activités, 2010)
Health and work problems are generally addressed through the potentially harmful effects of work on psychosomatic health. The purpose of this research is to look at the experience of work as put to the test by chronic illness and the importance of work in helping people to prevent the illness from taking the upper hand. The qualitative study, within the socio-clinical work psychology field, took a diachronic approach: three semi directive interviews with each person (64 individuals with varied employment situations, social and professional groups, ages and genders) and frequent meetings with charity organisations. People living with HIV and/or HCV are used to organising various private and public aspects of their lives. Breaking down barriers between the world of work and other areas of life enables us to pinpoint the adjustments, trade-offs and compromises that take place, as well as the resources and skills people acquire and how these are used and adjusted from one area to the next. The focus here is on the tasks of maintaining health, seeking and maintaining employment, and on the role of charities.